156k views
4 votes
Please help!!!
Which expression is equivalent to (3m^-1n^2)^4/(2m^-2n)^3

User Onyambu
by
4.7k points

2 Answers

2 votes

\text{Use:}\\\\(a\cdot b)^n=a^nb^n\\\\(a^n)^m=a^(n\cdot m)\\\\(a^n)/(a^m)=a^(n-m)


((3m^(-1)n^2)^4)/((2m^(-2)n)^3)=(3^4(m^(-1))^4(n^2)^4)/(2^3(m^(-2))^3n^3)=(81m^(-4)n^8)/(8m^(-6)n^3)\\\\=10.125m^(-4-(-6))n^(8-3)=10.125m^2n^5
User Faycal
by
5.4k points
4 votes

The answer on edg is B!

Hope this helps!

User Brm
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.